Factors associated with ultra-processed foods consumption in a cohort of Brazilian pregnant women - Ana Claudia Santos Amaral Fraga; Mariza Miranda Theme Filha; Maria Pappaterra Bastos (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Nutrition during pregnancy is essential for the health of the pregnant woman, the development of the fetus, and the prevention of complications related to pregnancy and the postpartum period. This study described the factors associated with high consumption of ultra-processed foods among pregnant women. This prospective cohort study was performed from February 2016 to November 2019 in two health units in the city of Rio de Janeiro, Brazil, with data from 344 pregnant women. The first interview was conducted in the prenatal visit at less than 20 gestational weeks, the second at 34 gestational weeks, and the third at two months postpartum. Diet was assessed in the last interview using a food frequency questionnaire, and food items were classified according to NOVA. The percentage of ultra-processed foods consumption was estimated by tertile distribution, and the third tertile represented the highest consumption. Based on the hierarchical analysis model, the associations between ultra-processed foods consumption and sociodemographic, reproductive health, pregestational, behavioral, and pregnancy variables were assessed using a multinomial logistic regression model. Older women had lower ultra-processed foods consumption (OR = 0.33; 95%CI: 0.15-0.71). Few years of schooling (up to 7 years; OR = 5.58; 95%CI: 1.62-19.23), history of a previous childbirth (OR = 2.48; 95%CI: 1.22-5.04), history of two or more previous childbirths (OR = 7.53; 95%CI: 3.02-18.76), and no history of regular physical activity before pregnancy (OR = 2.40; 95%CI: 1.31-4.38) were risk factors. The identification of risk and protection factors allows for the establishment of control measures and encouragement of healthy practices during prenatal care.